Bipolar Fuzzy Magnified Translations in Groups - U. Venkata Kalyani; T. Eswarlal; K. V. Narasimha Rao; A. Iampan (International Journal of Analysis and Applications, 2022)
In this paper, we define a bipolar fuzzy magnified translation (BFMT) of a bipolar fuzzy subgroup (BFSG) of a group. Based on this concept we have also developed some important results and theorems on bipolar fuzzy groups.